Kebijkan PPDB Zonasi dalam lembaga pendidikan di Indonesia - Rokhman, Arif Nur (Maliki Interdisciplinary Journal, 2024)
The policy of New Student Admission (PPDB) based on zoning has been receiving special attention in the Indonesian education system. This article discusses the zoning-based PPDB policy in Indonesia and its impact on the education system. The zoning method aims to reduce educational access disparities, equalize opportunities, and promote inclusivity. Despite the importance of these objectives, the zoning policy also presents various challenges and controversies. In this article, we analyze the factors influencing the success of the zoning-based PPDB policy, such as infrastructure, resource allocation, and education quality in each region. We also highlight emerging issues, including registration distortions, socio-economic influence, and curriculum adjustments. Research findings indicate that although the zoning policy has a positive impact on educational inclusivity, there is still a need for infrastructure and education quality improvement to achieve desired goals. Addressing registration distortions and enhancing public understanding of this policy are also key to its success. The zoning-based PPDB policy needs continuous evaluation and adaptation to better cater to the needs of each region. Increased participation of all stakeholders, including the government, schools, parents, and the community, will contribute to achieving a fair and high-quality education system in Indonesia.